2017
DOI: 10.1016/j.ebiom.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Activation of Heat Shock Protein 70 by Allosteric Regulation Provides an Insight into Efficient Neuroinflammation Inhibition

Abstract: Heat shock protein 70 (Hsp70) is widely involved in immune disorders, making it as an attractive drug target for inflammation diseases. Nonselective induction of Hsp70 upregulation for inflammation therapy could cause extensive interference in inflammation-unrelated protein functions, potentially resulting in side effects. Nevertheless, direct pharmacological activation of Hsp70 via targeting specific functional amino acid residue may provide an insight into precise Hsp70 function regulation and a more satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…Human monocyte-derived macrophages transfected with Hsp70 followed by exposure to LPS expressed less TNF-α, IL-1β, IL-12 and IL-10 at mRNA level, but not IL-6, compared to macrophages transfected with Hsp70 anti-sense DNA [22]. Nevertheless, in the murine microglial cell line BV-2, the pharmacological activation of Hsp70 by handelin significantly blocked the secretion of the pro-inflammatory cytokines TNF-α, IL-1β and IL-6 [19]. In our study of canine macrophage cells, we found that the LPS-induced upregulation of TNF-α and IL-6 mRNA was dramatically diminished upon cell stress.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Human monocyte-derived macrophages transfected with Hsp70 followed by exposure to LPS expressed less TNF-α, IL-1β, IL-12 and IL-10 at mRNA level, but not IL-6, compared to macrophages transfected with Hsp70 anti-sense DNA [22]. Nevertheless, in the murine microglial cell line BV-2, the pharmacological activation of Hsp70 by handelin significantly blocked the secretion of the pro-inflammatory cytokines TNF-α, IL-1β and IL-6 [19]. In our study of canine macrophage cells, we found that the LPS-induced upregulation of TNF-α and IL-6 mRNA was dramatically diminished upon cell stress.…”
Section: Discussionmentioning
confidence: 94%
“…Inducible Hsp70 is a representative member of the family of HSPs, and has been largely examined for its functions in stressed human and murine macrophages [ 16 , 17 , 18 ]. The upregulation of Hsp70 by inducers such as celastrol was shown to inhibit the production of pro-inflammatory cytokines, such as TNF-α, IL-6 and IL-1β in BV2 cells [ 19 ], human retinal pigment epithelial cells [ 20 ], and human alveolar macrophages [ 21 ]. Similarly, the overexpression of Hsp70 attenuates LPS-induced cytokine expression in macrophages [ 22 ] and microglia cells [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OGD/R, MTT, LDH release, Hoechst 33258 staining, AO/EB staining, Western blotting, transmission electron microscope, tryptophan fluorescence quenching study, Co-IP, DARTS, mitochondrial depolarization, and CD analysis assays were performed as previously described 59-60.…”
Section: Methodsmentioning
confidence: 99%
“…Hsp70 has been implicated in T cell regulation of various chronic inflammatory diseases, including rheumatoid arthritis (Van Eden et al 2005), colitis (Tanaka et al 2007), neurodegenerative diseases (Van Noort 2008), and experimental autoimmune uveoretinitis (Kitamei et al 2007), which makes the molecule a potential therapeutic target in chronic inflammations. Moreover, overexpression of Hsp70 was reported to play an essential role in regulation of apoptosis (Beere et al 2000;Saleh et al 2000) and protection against inflammation (Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%